KAPALLI’ SEBAGAI SEBUAH SKEMA ETIS SEORANG AUDITOR - Wijorse, Baby Yuliandani; Tenriwaru; Hajering (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to describe the role of Kapalli' jekkong culture on auditor ethics indecision making. This study uses a descriptive qualitative approach. This researchis located at the Office of the Inspectorate of the Selayar Islands Regency. Theinformants in this study were 8 people consisting of 5 auditors and 3 principalsfrom Selayar backgrounds. This study uses primary data obtained throughinterviews and observations. Data were analyzed using descriptive analysismethod. The results showed that Kapalli' is one of the social rules of the Selayarpeople, which is used as a way for parents to educate their children, Kapalli' isbelieved to be able to shape character for the better, because Kapalli' candiscipline those who apply it, by implementing Kapalli' jekkong has shaped theauditor's character to behave honestly, fairly, trustworthy and responsible, therebymaintaining integrity, objectivity, confidentiality, competence and prudence as wellas professional behavior within the auditor..